The Relationship between Perceived Organisational Support, Perceived External Prestige, Growth Need Strength and Job Satisfaction of Nurses in Pakistan - Yahya, Farzan; Rashid, Amad; Ali, Syed Atif (The journal of contemporary issues in business and government, 2017)
The purpose of the study is to explore the moderating role of Growth Need Strength (GNS) on the relationship between Perceived Organisational Support (POS), Perceived External Prestige (PEP) and job satisfaction in the healthcare industry of Pakistan. The data was collected from nurses working in the public sector hospitals in Pakistan. After a successful confirmatory data analysis, a multivariate regression analysis was utilised to interpret the results. The results indicate that there is a positive and statistically significant effect of POS and GNS on job satisfaction. However, no statistically significant association is found between PEP and job satisfaction. The findings also reveal that GNS positively moderates the relationship between POS and job satisfaction. Healthcare organisations can utilise these results as a basis for future planning and decision making to retain nurses and to improve their job satisfaction level. These organisations should give preference to employees with high growth needs.